Indonesian Local Wisdom: Reading Materials to Develop Students Character Education and 4C Skills - Sulistyani Sulistyani; Khoiriyah Khoiriyah (Universitas PGRI Madiun, 2025)
This study looked at how local wisdom reading materials in Indonesia support character education and the four Cs of the 21st century: creativity, critical thinking, teamwork, and communication. The study is classified as library research and uses a descriptive qualitative methodology. The